2018
DOI: 10.3892/ijo.2018.4410
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profiling regulates necroptotic cell death in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive types of cancer and is among the leading causes of cancer-related mortality worldwide. Although the dysregulation of microRNAs (miRNAs or miRs) has often been reported in HCC, the precise molecular mechanisms by which miRNAs modulate the process of tumorigenesis and the behavior of cancer cells are not yet clearly understood. In this study, we identified a novel three‑miRNA signature, including miR‑371-5p, miR‑373 and miR‑543, that appears to orchest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…In human epithelial cells, overexpression of miR-214-3p downregulates caspase-1, and the miRNA is downregulated in cataract lens anterior capsular tissues (59). MiR-371a-5p, miR-373-3p, and miR-543-3p have been proposed to enhance TNF-a-induced cell death by targeting the noncanonical caspase-8 inflammasome, and they are overexpressed in hepatocellular carcinoma tissue (60). However, the miRNA-driven regulation of further human inflammasome components, such as other NLR sensor molecules, AIM2, caspase-4, and caspase-5, has so far not been investigated in specific experimental studies.…”
Section: Mirnas Target Inflammasome Componentsmentioning
confidence: 99%
“…In human epithelial cells, overexpression of miR-214-3p downregulates caspase-1, and the miRNA is downregulated in cataract lens anterior capsular tissues (59). MiR-371a-5p, miR-373-3p, and miR-543-3p have been proposed to enhance TNF-a-induced cell death by targeting the noncanonical caspase-8 inflammasome, and they are overexpressed in hepatocellular carcinoma tissue (60). However, the miRNA-driven regulation of further human inflammasome components, such as other NLR sensor molecules, AIM2, caspase-4, and caspase-5, has so far not been investigated in specific experimental studies.…”
Section: Mirnas Target Inflammasome Componentsmentioning
confidence: 99%
“…In HBV or HCV infections, dysregulation of miR-146a promotes liver inflammation and disease progression, in contrast to the usual role of miR-146a in suppressing cancer growth and inhibiting inflammation (1618,51,52). The finding that miR-371, miR-373 and miR-543 dramatically decreased caspase-8 (Casp-8) gene expression in HCC, by binding to the Casp-8 mRNA, supports the pro-necrotic and pro-inflammatory functions of miRNAs (53). Furthermore, Visalli et al (53) identified that miR-371, miR-373 and miR-543 were overexpressed in HCC, resulting in a significantly decreased level of Casp-8, a marked increase in programmed cell necrosis and an intensive inflammatory process.…”
Section: Role Of Mir-146a In Hccmentioning
confidence: 84%
“…L. P Liu, Yang, et al (2017). andXiu, Wang, Wang, Ji, and Zhang (2019) confirmed the low expression of miR-543 in tissue samples of hepatocellular carcinoma (HCC), whileVisalli et al (2018) found upregulation of miR-543 expression in tissue samples from patients with HCC Dang, Zheng, Liu, Wu, and Wu (2017). found that the expression level of miR-543 was upregulated in cervical cancer tissue, while X Liu, Gan, and Zhang (2019).…”
mentioning
confidence: 82%
“…In contrast, L. P. Liu, Yang, et al (2017) found that miR‐543 could target ubiquitin‐conjugating enzyme E2T (UBE2T), which, in turn, inhibits p53 protein degradation and HCC cell proliferation. Visalli et al (2018) believed that miR‐543 was involved in the inhibition of negative necroptotic regulator caspase‐8 (Casp‐8) and eventually promotes necrotic apoptosis of HCC cells. Similarly, Xiu et al (2019) found that miR‐543 expression could reduce the proliferation of HCC cells and promote the apoptosis of HCC cells.…”
Section: The Role Of Mir‐543 In Human Cancermentioning
confidence: 99%